Efektivitas Penggunaan Podcast dalam Meningkatkan Pemahaman Pembelajaran Fiqih di Era Digitalisasi Siswa Kelas VII D MTs Al Ikhlas Bontang Tahun Pelajaran 2023/2024 - Komaningsih, Tri; Minarsih, Minarsih (NABAWI: Jurnal Penelitian Pendidikan Islam, 2024)
This study aims to provide an overview of the effectiveness of using Podcasts as a learning medium, focusing on enhancing students' understanding of fiqh. In the ever-evolving digital era, innovation in teaching methods becomes increasingly important to improve the quality of education, and Podcasts have gained attention as a valuable tool in various educational fields, including fiqh learning. This research employs a descriptive qualitative method, with data collection techniques through observation, interviews, and documentation. The research focuses on seventh-grade students in class VII D. The results indicate the effectiveness of using Podcasts in fiqh learning, including making learning more engaging, interactive, and supportive of independent study. There is an increase in learning effectiveness by combining conventional methods with Podcast use, along with support from infrastructure and parents. The students' understanding of fiqh significantly improves, with students showing more interest and interaction in learning and being able to apply fiqh concepts in their daily lives. It is concluded that the use of Podcasts is effective in enhancing students' understanding of fiqh, making learning more engaging, interactive, and applicable to everyday life.